5G as Enabler for Industrie 4.0 Use Cases: Challenges and Concepts - Gundall, Michael; Schneider, Jorg; Schotten, Hans D.; Aleksy, Markus; Schulz, Dirk; Franchi, Norman; Schwarzenberg, Nick; Markwart, Christian; Halfmann, Rudiger; Rost, Peter; Wubben, Dirk; Neumann, Arne; et al. (Proceedings (IEEE International Conference on Emerging Technologies and Factory Automation), 2018)
The increasing demand for highly customized products, as well as flexible production lines, can be seen as trigger for the "fourth industrial revolution", referred to as "Industrie 4.0". Current systems usually rely on wire-line technologies to connect sensors and actuators. To enable a higher flexibility such as moving robots or drones, these connections need to be replaced by wireless technologies in the future. Furthermore, this facilitates the renewal of brownfield deployments to address Industrie 4.0 requirements. This paper proposes representative use cases, which have been examined in the German Tactile Internet 4.0 (TACNET 4.0) research project. In order to analyze these use cases, this paper identifies the main challenges and requirements of communication networks in Industrie 4.0 and discusses the applicability of 5th generation wireless communication systems (5G).